Tindakan Preventif Pesantren dalam Menghadapi Kenakalan Remaja (Studi Analisis Di Pondok Pesantren Nurul Haramain NWDI Putra Narmada) - Muh. Asroruddin al Jumhuri (Sekolah Tinggi Agama Islam al-Amin, Gersik, Kediri, Lombok Barat, NTB, 2020)
Islamic boarding schools in their development and development have educational principles consisting of universal truth values ​​and play an important role and always create peace, comfort and harmony. So that it can become the main characteristic of pesantren as a culture.However, seeing the ever-increasing developments in daily life, the boarding school tries to educate students to be able to adjust to the current situation, so that they do not follow current developments. However, sooner or later, whether intentionally or not, various cultures will have an influence on the students. This influence can have an impact both on the socio-political life, security, education and also on the morality of the students, this impact can be positive or negative.The formulation of the problems of this study are as follows: 1) What types of juvenile delinquency affect the lives of students at the Nurul Haramain Islamic Boarding School, NWDI Putra Narmada ?, and 2) What preventive measures does Nurul Haramain Islamic Boarding School NWDI Putra Narmada use in dealing with juvenile delinquency? This research is a descriptive study, namely research that aims to obtain a complete picture of the whole subject and object under study.Based on the results of interviews and observations made by the author during the research location, it can be identified that there are two ways or efforts made by the Nurul Haramain Islamic Boarding School NWDI Putra Narmada in dealing with juvenile delinquency. 1) Internal efforts, namely the efforts made by the Nurul Haramain Islamic Boarding School, NWDI Putra Narmada, whose activities are more focused on students with the aim of fostering and directing students according to Allah's orders and Rasullulloh or according to Al-Quran and As-Sunnah such as routine recitation. , Night prayers and spiritual taujih-tujih to awaken and foster the morals of the santri. and 2) Efforts that are external in nature which include the efforts made by the Nurul Haramain Islamic Boarding School NWDI Putra Narmada in order to carry out its function as a religious institution that does not only preach in the pesantren environment but also actively conducts activities for the communities around it. .